Tensile properties of kenaf/unsaturated polyester composites filled with a montmorillonite filler - Rozman, Haji Din, Prof.; Luqman, Musa, Dr.; Azniwati, A. A.; Rozyanty, Abdul Rahman (Wiley Periodicals, Inc., 2011)
Link to publisher's homepage at http://onlinelibrary.wiley.com/